Evaluating community perception and the impact of the billion tree afforestation project on key medicinal plants in Buner forest division, KP, Pakistan - Khalid, Faisal (Review of Plant Studies, 2025)
Pakistan is a country of remarkable ecological and cultural diversity, featuring a wide range of climates, landscapes, and rich biodiversity from towering mountains and vast deserts to fertile plains and lush forests. To gain a better understanding of community perspectives, identify the primary threats to medicinal plants, and assess the impact of the Billion Tree Afforestation Project (BTAP) on medicinal plant conservation in the Buner Forest Division, this study was conducted for the first time in the region. A total of 28 sample plots were surveyed inside 14 BTAP-established closures, while another 28 plots were assessed in areas where no BTAP activities had taken place. In addition, a rapid assessment approach was employed, involving interviews with 200 local community members. The results revealed that the relative density of medicinal plant species was significantly higher inside the closures (92.25%) compared to outside (7.75%). Similarly, the relative cover of medicinal plants was greater within the closures (97.83%) than in non-protected areas (2.17%). The relative frequency of medicinal plant species also followed the same pattern, with a higher value inside the closures (83.46%) versus outside (16.54%). These findings demonstrate that the establishment of closures has a positive impact on the regeneration of medicinal plants and trees. By restricting activities such as grazing, browsing, cutting, and plant collection, closures contribute significantly to biodiversity conservation. Preserving and protecting our natural heritage is essential, as it plays a vital role in sustaining the ecological balance and supporting local livelihoods.